O processo crime dos inconfidentes: entre os registros oficiais e a literatura - Renata Esteves Furbino (2011)
This study aims to investigate possible interaction among History, Legal Procedure and Literature, seeking to understand the methodological premises of the historical doing and of the legal-historical doing, mainly with regard to the modus of producing the history of Brazilian Criminal Procedure. At first, two important historiographical strands are examined – the so-called positivist school and the Annales School – alongside with some versions of the Inconfidência Mineira presented under the glances of Law, History and Literature. Among the approached writings one may find works by Kenneth Maxwell, João Pinto Furtado e André Figueiredo Rodrigues. The analysis of these versions reflects the existence of a colonial law, which translates the characteristics of the Portuguese monarchy and points out to the cruel methods of punishment used by the Portuguese empire to reassert their power over the colony during the conspiracy trial. As for conclusion, the criminal procedure is conceived as a kind of social fiction, without disregarding however, the distinctions and similarities among literary, historical and procedural narratives.